Vitamin D as The Primary Predictor of Perceived Stress Levels In Bipolar Disorder - Siti Wahyuni; Rohmaningtyas Hidayah Setyaningrum; Emika Ambar Pangesti; Indria Hafizah; Farida Murtiani (Public Health of Indonesia, 2026)
Background: An individual's perception of a situation plays a large role in determining the level of perceived stress. Previous studies have shown that bipolar disorder patients have higher levels of perceived stress than healthy individuals. A number of biological, psychosocioeconomic and environmental factors are thought to influence stress perception in bipolar patients. Objective: This study aimed to determine the factors that influence stress perception in bipolar patients. Methods: This study is an observational study with cross sectional desaign. Thirty-two bipolar disorder patients who met the inclusion and exclusion criteria during August - September 2024 at the Psychiatry outpatient installation of UNS Hospital measured stress perception with the Perceived Stress Scale 10 form. Data normality was tested with Shapiro Wilk. Data were tested for correlation with Pearson product moment if normally distributed, and Spearman rank if not normally distributed, while nominal data used the eta correlation test. Then continued multivariate analysis of multiple linear regression. Results: Variables that are significantly correlated with PSS-10 scores are vitamin D levels (r = 0.587; p =0.001), occupation (r = 0.400; p = 0.023), income (r = 0.407; p = 0.021) and moderate correlation strength (r = 0.400 to -0.599). The variable that has the most significant effect on perceived stress of bipolar patients is vitamin D levels (B =-0.164; p=0.043), This indicates that for every one-unit increase in vitamin D level, the PSS-10 score decreases by 0.167 points. Conclusion: There are factors that correlate with stress perception in bipolar patients, namely vitamin D levels, occupation, and income. The variable that has the most significant effect on stress perception of bipolar patients is vitamin D levels.